2012
DOI: 10.1371/journal.pone.0048086
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Osteosarcoma Expression Phenotype by MicroRNAs

Abstract: BackgroundOsteosarcomas are the most common primary malignant tumors of bone and show multiple and complex genomic aberrations. miRNAs are non-coding RNAs capable of regulating gene expression at the post transcriptional level, and miRNAs and their target genes may represent novel therapeutic targets or biomarkers for osteosarcoma. In order to investigate the involvement of miRNAs in osteosarcoma development, global microarray analyses of a panel of 19 human osteosarcoma cell lines was performed.Principal find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
215
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(229 citation statements)
references
References 58 publications
8
215
1
1
Order By: Relevance
“…Although previous data demonstrated that miR-142 was downregulated in OS cell lines, as detected by global microarray analyses (17), the role of miR-142 in OS remains unknown.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although previous data demonstrated that miR-142 was downregulated in OS cell lines, as detected by global microarray analyses (17), the role of miR-142 in OS remains unknown.…”
Section: Discussionmentioning
confidence: 94%
“…Although miR-142 has been found to be downregulated in OS cell lines (17), the role and epigenetic mechanisms of miR-142 in OS remain unknown. The aim of the present study was to compare the expression of miR-142 between OS and pericancerous tissues and investigate the role of epigenetic regulation in the decreased expression of miR-142 in OS.…”
Section: Introductionmentioning
confidence: 99%
“…29 The molecular mechanisms underlying miR-9 and the regulation of osteosarcoma carcinogenesis remain unclear and require further study.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-17-92 cluster composed of seven miRNAs (miR-17-5p, miR-17-3p, miR-18a, miR-19a, miR-20a, miR-19b, and miR-92-1) [16,17]. Recent studies have observed that the miR-17-92 cluster is overexpressed in several types of cancer [18][19][20]. Studies also have shown that overexpression of miR-17-92 cluster may regulate cell cycle, apoptosis, invasion, and proliferation in many types of human cancer [21,22].…”
mentioning
confidence: 99%